Generalised anxiety and depression during COVID-19 pandemic among post-metric science students at Baramulla - Syed Nasir Ahmad Gilani,; Ain, Syed Najmul; Gilani, Mohamad Azhar (International Journal of Research in Medical Sciences, 2023)
Background: COVID-19 pandemic has greatly affected the studies of students because of strict lockdown and closure of schools. As such students might have developed a lot of stress. Primary objective of this study was to find out the prevalence of generalized anxiety and depression during the COVID-19 pandemic among post-metric science students at Baramulla preparing for professional exams after senior secondary. Methods: This cross-sectional study was conducted by distributing a pre-designed questionnaire among post-metric science students at Baramulla, Kashmir. Two tuition centres were randomly selected out of all the centres. All the students who returned filled questionnaires were included. Binary logistic regression was employed to find the association of anxiety and depression with independent variables. Results: Of the 173 participants, 91 were male (52.6%), the mean age was 16.9±1.4 years. For 81% of students, the pandemic had negatively affected their studies. About 16% (28) students had severe anxiety whereas 33% (57) had moderate anxiety and 14 students (8%) had severe depression whereas 23 (13%) had moderately severe depression. Those who did not perform routine exercise daily had higher odds of depression (AOR=2.86) and anxiety (AOR=2.3). Conclusions: Anxiety and depression levels among young students as high as found in this study cannot be ignored. A habit of routine exercise that may have been hampered during the current pandemic must be inculcated among youngsters for healthier mental health.